Discovery of Bis-sydnone styryl ketone as a selective cyclooxygenase-2 inhibitor - Abdualrahman Mohammed Abdualkader; Muhammad Taher; Nik Idris Nik Yusoff; Mohamed Alaama (SpringerOpen, 2021)
Abstract Background Various literature sources have documented a wide spectrum of therapeutic properties of sydnones including anti-inflammatory, anticancer, antimicrobial activities. Phenyl styryl ketones and their derivatives as members of the chalcone family have also been reported as significant bioactive molecules. The current study was initiated to evaluate the anti-inflammatory activity of sydnone-based compounds including some novel bis-sydnone styryl ketone hybrids. Results Twenty-five sydnone-containing compounds were successfully synthesized. Compounds 46-48 and 56-58 were reported as new sydnone derivatives. Whereas, compounds 61-63 were synthesized as novel molecules containing two sydnone rings linked via α,β-unsaturated ketone. The structures of the synthesized compounds were confirmed by FTIR, 1H NMR, 13C NMR and ToF-MS analyses. The in vitro COX inhibition assay showed varied activity. Compounds 47, 51, 58 and 63 showed the most potent COX inhibitory effects at a concentration of 200 μM. The selectivity index revealed that 63 was the best selective COX-2 inhibitor. Acetylation of the sydnone ring at C-4 was fruitful for the COX inhibitory effects. Docking analysis showed that COX-2 selectivity was due to a favourable positive charged interaction occurring between the sydnone ring of 63 and Arg513 of COX-2. Compound 51 was hydrogen bonded to Arg513. On the other hand, the low inhibitory effect of 63 against COX-1 was due to an unfavourable polar interaction with His513 in the binding pocket of COX-1. Conclusions The compounds were successfully synthesized and characterized. Compound 63 had a common architecture and pharmacophoric features with known selective COX-2 inhibitors (the coxib family) which make it a suitable candidate for the designing of selective and safe NSAID.